2011
DOI: 10.1039/c1jm10918a
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of zinc oxide nanostructures through kinetics control

Abstract: In-depth understanding of the kinetics of the vapor deposition process is substantial for advancing this capable bottom-up nanostructure synthesis approach into a versatile large-scale nanomanufacturing technology. In this paper, we report a systematic study of the vapor deposition kinetics of ZnO nanomaterials under controlled atmosphere and properly refined deposition conditions. The experiments clearly evidenced the self-catalyzed growth of ZnO NWs via the formation of ZnO nanoflowers. This result illustrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 52 publications
(89 reference statements)
0
24
0
Order By: Relevance
“…We recently synthesized green fluorescent ZnO nanowires (NWs), which could overcome the abovementioned hurdles, and demonstrated that the ZnO NWs can be employed for targeted imaging of cancer cells [44, 45]. The c(RGDyK) (abbreviated as RGD) peptide, which is a potent antagonist of integrin α v β 3 (a key protein involved in tumor angiogenesis and metastasis) [46, 47], was used as the targeting ligand.…”
Section: Bioimaging With Zno Nanomaterialsmentioning
confidence: 99%
“…We recently synthesized green fluorescent ZnO nanowires (NWs), which could overcome the abovementioned hurdles, and demonstrated that the ZnO NWs can be employed for targeted imaging of cancer cells [44, 45]. The c(RGDyK) (abbreviated as RGD) peptide, which is a potent antagonist of integrin α v β 3 (a key protein involved in tumor angiogenesis and metastasis) [46, 47], was used as the targeting ligand.…”
Section: Bioimaging With Zno Nanomaterialsmentioning
confidence: 99%
“…The deposition of ZnO consists of two different procedures, condensation and oxidation of zinc. At high temperatures (>1000 C), the oxidation rate is very faster than condensation [17]. Comparison between condensation and oxidation rate at different temperatures can help us to explain the formation of different ZnO nanostructures.…”
Section: Resultsmentioning
confidence: 96%
“…19 The fluorescent ZnO NPs coupled with PET imaging capacity can enable the in vivo monitoring of ZnO nanomaterials in biomedical applications. Compared with our previously developed green fluorescent ZnO nanowires, 20, 21 these red-fluorescing ZnO NPs possess better tissue penetration of the optical signal, making them more preferable for fluorescence-guided drug delivery purposes. However, the requirement of ultraviolet light excitation (excitation wavelength: ~350 nm) for their fluorescence limited their applications in vivo, which serves as the primary reason that no fluorescence imaging was performed in vivo in the current study.…”
Section: Discussionmentioning
confidence: 97%